2000
DOI: 10.1152/ajpheart.2000.279.1.h388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cardiotrophin-1 on hemodynamics and endocrine function of the heart

Abstract: Cardiotrophin-1 (CT-1), a member of the interleukin-6 superfamily of cytokines, possesses hypertrophic actions and atrial natriuretic peptide (ANP)-producing activity in vitro. The goal of our study is to elucidate whether CT-1 affects the cardiovascular system in vivo. Intravenous injection of CT-1 (4-100 microg/kg) in conscious rats evoked significant declines in blood pressure and reflex increases in heart rate (HR) in a dose-dependent manner. CT-1 induced no significant change in cardiac output (from 260.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 42 publications
(37 reference statements)
1
19
0
2
Order By: Relevance
“…Echocardiographic examination of LV function for 6 h after administration of CT-1 alone revealed it to have no positive or negative inotropic effects (data not shown). This is consistent with our recent findings that CT-1 has no effect on the maximum rate of rise (dP/dT) in LV developed pressure and perfusion pressure in the isolated perfused rat heart, 30 and confirms that the inhibitory effect of CT-1 on LPS-induced LV dysfunction is indirect.…”
Section: Ct-1 Pretreatment Protects Lps-induced LV Dysfunctionsupporting
confidence: 93%
“…Echocardiographic examination of LV function for 6 h after administration of CT-1 alone revealed it to have no positive or negative inotropic effects (data not shown). This is consistent with our recent findings that CT-1 has no effect on the maximum rate of rise (dP/dT) in LV developed pressure and perfusion pressure in the isolated perfused rat heart, 30 and confirms that the inhibitory effect of CT-1 on LPS-induced LV dysfunction is indirect.…”
Section: Ct-1 Pretreatment Protects Lps-induced LV Dysfunctionsupporting
confidence: 93%
“…20 We therefore tested whether in addition to attenuating STAT3 activation, pretreatment with CT-1 would also inhibit an integrated biological response, such as decline in BP. Figure 6A shows that whereas the first injection of CT-1 (20 g/kg body weight) elicited a clear decline in BP, a second injection 60 minutes later had a significantly smaller effect.…”
Section: Pretreatment With Ct-1 Inhibits the Hypotension Induced By Amentioning
confidence: 99%
“…13 CT-1 binds to the gp130-LIF receptor complex in myocytes, activating the JAK-STAT pathway and inducing hypertrophic responses. 14 -18 Other investigators 19 and we 20 recently reported additionally that the intravenous injection of CT-1 induces nitric oxide (NO)-dependent hypotension dosedependently in conscious rats. Taken together, these findings strongly suggest that CT-1 acts as a cytokine with a variety of important actions in the cardiovascular system.…”
mentioning
confidence: 96%
“…Infusion of exogenous CT-1 into adult animals provokes an acute decrease in blood pressure that stimulates a reflex increase in heart rate [32][33][34]. These acute effects of CT-1 do not include any changes in ventricular pressure or cardiac contractility.…”
Section: Discussionmentioning
confidence: 99%